INITIAL PUBLIC OFFERING (IPO): TINJAUAN NON KEUANGAN TERHADAP TINGKAT UNDERPRICING - Nastiti, Nadila Tri; Sari, Shinta Permata (ITB AAS Indonesia Surakarta, 2024)
Initial Public Offering is a company's initial effort to attract investors on the stock exchange. In the stock offering, the company will get public attention to buy its shares by setting a lower initial stock price. This research objective is to analyze the effect of non-financial variables on the level of underpricing in go public companies that conduct Initial Public Offering. Non-financial variables used in research include underwriter reputation, aditor reputation, company age, oversubscription, and independence of the board of commissioners. The samples are 64 companies which are sourced from secondary data collected by purposive sampling method during 2021-2023. The data is processed with multiple regression analysis. The results show that the underwriter reputation has an effect on the level of underpricing, meanwhile auditor reputation, company age, oversubscription, and independence of the board of commissioners have insignificant effect on the level of underpricing. Keywords : underpricing, underwriter reputation, auditor reputation, company age, oversubscription, independence of the board of commissioners.